Science case for the Asteroid Impact Mission (AIM): A component of the Asteroid Impact & Deflection Assessment (AIDA) mission. Issue 12 (15th June 2016) - Michel, Patrick; Cheng, A.; Küppers, M.; Pravec, P.; Blum, J.; Delbo, M.; Green, S.F.; Rosenblatt, P.; Tsiganis, K.; Vincent, J.B.; Biele, J.; Ciarletti, V.; et al.
Abstract: The Asteroid Impact & Deflection Assessment (AIDA) mission is a joint cooperation between European and US space agencies that consists of two separate and independent spacecraft that will be launched to a binary asteroid system, the near-Earth asteroid Didymos, to test the kinetic impactor technique to deflect an asteroid. The European Asteroid Impact Mission (AIM) is set to rendezvous with the asteroid system to fully characterize the smaller of the two binary components a few months prior to the impact by the US Double Asteroid Redirection Test (DART) spacecraft. AIM is a unique mission as it will be the first time that a spacecraft will investigate the surface, subsurface, and internal properties of a small binary near-Earth asteroid. In addition it will perform various important technology demonstrations that can serve other space missions. The knowledge obtained by this mission will have great implications for our understanding of the history of the Solar System. Having direct information on the surface and internal properties of small asteroids will allow us to understand how the various processes they undergo work and transform these small bodies as well as, for this particular case, how a binary system forms. Making these measurements from up close and comparing them with ground-based data from telescopes will also allow us to calibrate remote observations and improve our data interpretation of other systems. With DART, thanks to the characterization of the target by AIM, the mission will be the first fully documented impact experiment at asteroid scale, which will include the characterization of the target's properties and the outcome of the impact. AIDA will thus offer a great opportunity to test and refine our understanding and models at the actual scale of an asteroid, and to check whether the current extrapolations of material strength from laboratory-scale targets to the scale of AIDA's target are valid. Moreover, it will offer a first check of the validity of the kinetic impactor concept to deflect a small body and lead to improved efficiency for future kinetic impactor designs. This paper focuses on the science return of AIM, the current knowledge of its target from ground-based observations, and the instrumentation planned to get the necessary data.